Increased Uncertainty Environment During the COVID-19 Pandemic Period and Its Effect on Key Audit Matters: BIST 100 Companies Analysis - Deniz Özbay (Muhasebe Enstitüsü Dergisi)
The Key Audit Matters (KAMs) section of the audit report aims to provide more information to stakeholders about important and critical matters in the audit process, thereby contributing to the preparation of more transparent and high-quality audit reports. The auditor explains any matters relating to uncertainty and risk in the KAM paragraph. This study aims to examine the effect of increasing levels of uncertainty in this environment during the COVID-19 period on the KAMs disclosures of the BIST-100 companies. In line with this purpose, the KAMs disclosures of companies for 2019 and 2020 were compared and the results were interpreted. The content analysis technique was used in the study and data were collected from independent audit reports of companies. According to the results “revenue recognition”, “financial instruments”, and “property, plant and equipment” were the most frequently reported topics in the KAMs for both periods. Furthermore, it was determined that the share of accounting estimates, which were expected to be most affected by uncertainty, increased in the KAM paragraphs.